Nanoparticles based on PLGA and its coâ€polymer: An overview - Muthu, MS (Asian Journal of Pharmaceutics (AJP), 2014)
Poly (D, L-lactide-co-glycolide) (PLGA) is approved by the Food and Drug Administration for drug delivery use. The polymeric nanoparticles based on PLGA and its co-polymer are designed for controlled and targeted drug delivery. Also, PLGA and its co-polymer are important in designing nanoparticles with desired characteristics such as biocompatibility, biodegradation, particle size, surface properties, drug release and targetability.This review focuses on the polymer literature, methods for preparation of nanoparticles and recent studies on the nanoparticles based on PLGA and its co-polymer for the conventional and targeted delivery of drugs by various routes.